Decoding the future: genomic sequencing's vital role in communicable disease prevention within public health practice - a scoping review - Harun, Amin; Md Zamri, Ahmed Syahmi Syafiq; Zamberi, Mohd Zafrullan; Za’bah, Abi Khairul Aizad; Abd Aziz, Siti Fatimah; Ahmad Fauzi, Fatimah; Mahmud, Aidalina; Abdul Rahman, Anita (Faculty of Medicine, International Islamic University Malaysia, 2024)
Precision public health using genomic sequencing is a new field that has been gained interest by public health practitioner for prevention and control measures. The objective of this study is to identify the various applications of genomic sequencing for prevention of communicable disease in public health practice. Articles containing relevant keywords were identified using a systematic search strategy applied in Medline, Scopus, and Springer electronic databases. Full text of included in the study were retrieved and categorized. A total of 24 articles were included in the final review. The main themes regarding application of genomic sequencing in the prevention of communicable disease that was found in the articles were describing transmission patterns, investigating outbreaks, diagnosing infection, developing and evaluating interventions including vaccines, outcomes response treatment and monitoring antimicrobial resistance. In conclusion, genomic sequencing has the potential to enhance the prevention and control of communicable diseases globally.